Andrey Platonov and Literary Institutions. On the Question of Commenting on the Works of the Socialist Reconstruction Era - Daria S. Moskovskaya (Studia Litterarum)
The profession of electric engineer gave Platonov an opportunity to be a writer and feel independent from literary groups in the 1920s. In the 1930s, he becomes a member of different literary associations. In these years, Platonov’s discourse undergoes different changes. His new vocabulary, whether normative and neutral (humanist, stratum, trifle, comrade) or non-normative (fool, scoundrel) reveals his dialogue with the regime that the writers’ unions were standing for. Platonov’s use of words demonstrates not “things” themselves but his attitude to them, and shows a new ideological borderline that the country had crossed in the year of the “great turning point.” Battles for a new language initiated by the Soviet regime immediately after October Revolution reached its apotheosis at that moment. The language reflected the crisis of worldviews, lifestyles, and values. The new meaning of the neutral vocabulary defines the structure and plot of Platonov’s works in the 1930s. Platonov turns to the language of literary organizations that were developing a new “language standard” as a form of social domination.